Is pre‐transplant sensitization against angiotensin II type 1 receptor still a risk factor of graft and patient outcome in kidney transplantation in the anti‐HLA Luminex era? A retrospective study. (5th October 2017) - Deltombe, Clement; Gillaizeau, Florence; Anglicheau, Daniel; Morelon, Emmanuel; Trébern‐Launay, Katy; Le Borgne, Florent; Rimbert, Marie; Guérif, Pierrick; Malard‐Castagnet, Stéphanie; Foucher, Yohann; Giral, Magali
Summary: We aimed to assess the correlation of anti‐angiotensin II type 1 receptor antibodies (anti‐AT1R‐Abs) before transplantation on a multicentric cohort of kidney transplant recipients (2008–2012), under tacrolimus and mycophenolate mofetil (MMF), screened by Luminex technology for anti‐HLA immunization. Anti‐AT1R antibody levels were measured by ELISA in pretransplantation sera of 940 kidney recipients from three French centers of the DIVAT cohort. Multivariable Cox models estimated the association between pretransplant anti‐angiotensin II type 1 receptor antibodies and time to acute rejection episodes (ARE) or time to graft failure. Within our cohort, 387 patients (41.2%) had pretransplant AT1R‐Abs higher than 10 U/ml and only 8% (72/970) greater than 17 U/ml. The cumulative probability of clinically relevant (cr)‐ARE was 22.5% at 1 year post‐transplantation [95% CI (19.9–25.4%)]. The cumulative probability of graft failure and patient death were 10.6% [95% CI (8.4–13.3%)] and 5.7% [95% CI (4.0–8.1%)] at 3 years post‐transplantation, respectively. Multivariate Cox models indicated that pretransplant anti‐AT1R antibody levels higher than 10 U/ml were not significantly independently associated with higher risks of acute rejection episodes [HR = 1.04, 95% CI (0.80–1.35)] nor with risk of graft failure [HR = 0.86, 95% CI (0.56–1.33)]. Our study did not confirm an association between pretransplant anti‐AT1R antibody levels and kidney transplant outcomes.